PEMAHAMAN GENDER ANGGOTA DPRD PEREMPUANPROVINSI NTT DALAM PROSES LEGISLASI PERDA NOMOR 7 TAHUN 2016 - Mamoh, Theo Philips J G D K; Ali Azhar, Muhammad; Noak, Piers Andreas (Jurnal Nawala Politika; 2018, 2018)
ABSTRA CT Female legislator knowledge about gender is one of the problem in Indonesia, especially at Regional House of Representative (as known as DPRD) Nusa Tenggara Timur. This research aims to find out the understanding from two female  legislators at Commission V DPRD Nusa Tenggara Timur to responses the overseas workforce  gender issues  and how they  fight for this case at  commission meeting. This research used some theories, first Liberal Feminism theory by Merry Wollstonecraft. Second, Political Representatives theory by MichealSaward. And the last is Rational Comprehensive theory by Hoogerwerf. This research also used Descriptive qualitative method which is to find  the data by observation, interview and document. Result from this research is the female legislators  at Commission V DPRD Nusa Tenggara Timur already understand about gender and they do their duties and responsibilities  as appropriate. Their performance has shown their ability and also the other females legislator from another commission to understand about gender issues and how to resolves the gender bias of Indonesia overseas workforce. The outcome from this understanding and female legislator performances at Regional House of representative NTT 2014-2019 is a local regulation has ratified by 2016. The local regulation content talk about Indonesian workers services and control , especially control and mechanism for Indonesia labor abroad. Keywords: Gender and Legislation Process